Identification and Analysis of 4G LTE Network Blind Spot Areas in the Papua Highlands Using Drive Test Method - Shafiya Adelina Harahap; Bashor Fauzan Muthohirin; Diah Risqiwati (Eduvest - Journal of Universal Studies, 2026)
The Papua Pegunungan region is one of the areas in Indonesia that still faces significant challenges in achieving equitable cellular network coverage, particularly for 4G LTE services. Its extreme geographical conditions, such as high mountains and limited infrastructure, are the main causes of blind spot areas that hinder communication and information access. This study aims to analyze the quality of the 4G LTE network and identify blind spot areas in the region using the Drive Test method. The technical parameters measured include RSRP (Reference Signal Received Power), SINR (Signal-to-Interference-plus-Noise Ratio), and throughput. Data collection was conducted using the G-NetTrack Pro application along predetermined routes. The results indicate several locations with very poor signal quality (categorized as Very Bad), particularly in areas far from base stations and obstructed by geographic features such as hills or dense forests. The collected data were mapped to visualize the signal strength distribution and delineate areas categorized as blind spots. This research is expected to serve as a basis for technical policy-making and network optimization planning by service providers to improve telecommunication access in remote and underserved regions